Effects of forest management on the conservation of bird communities in eastern North America: A meta‐analysis. Issue 1 (20th January 2023) - Akresh, Michael E.; King, David I.; McInvale, Savannah L.; Larkin, Jeffery L.; D'Amato, Anthony W.
Abstract: Forest management affects conditions for both early‐ and late‐seral organisms, and managers and conservationists require information for balancing the ostensibly opposing habitat needs of both these guilds. We conducted meta‐analyses that examined silvicultural systems with a range of postharvest retention and their impacts on mature‐forest and shrubland bird species densities in eastern North America during the breeding season. Densities of mature‐forest bird species generally declined as canopy tree retention and basal area decreased, although some mature‐forest species had similar densities among unharvested and partially harvested (e.g., first‐entry shelterwood) stands, and others had their highest densities in shelterwoods. We conducted a previous meta‐analysis study, which showed most shrubland bird species in the region increase with harvest intensity, but some shrubland species had similar densities in clearcuts and shelterwoods. Given the contrasting effects of harvest intensity on the two avian guilds, we used Partners‐in‐Flight conservation values to generate objective community‐wide conservation indices relative to postharvest tree retention. Clearcuts and shelterwoods typically had the highest conservation values, and unharvested and lightly thinned stands (70%–100% tree retention) had the lowest conservation scores. Many declining shrubland bird species of conservation concern are abundant in low‐retention stands, thus elevating the conservation value of these stands. Additionally, high conservation values of harvested stands with 40%–70% tree retention represent the presence of both shrubland and mature‐forest species; the latter are potentially responding to enhanced understory structure needed for avian nesting or foraging. In contrast, contemporary closed‐canopy forests in eastern North America are generally characterized by low structural diversity and are mid‐seral stands due to historical patterns of land use and tree harvesting. Although avian community conservation values were lowest in high‐retention stands and many other threatened, non‐avian taxa depend on open‐canopy, managed forests, managers should note that late‐seral, unharvested stands can provide important habitat for old‐growth‐dependent taxa and any intensive forestry should also take into account other factors. Considering the growing interest in using postharvest retention of canopy trees to meet ecological objectives, our novel synthesis can assist managers in assessing species‐specific and community‐wide avian responses to tree retention levels along the entire gradient of canopy treatments.